An evaluation of diffraction peak profile analysis (DPPA) methods to study plastically deformed metals. (5th December 2016) - Simm, T.H.; Withers, P.J.; Quinta da Fonseca, J.
Abstract: A range of diffraction peak profile analysis (DPPA) techniques were used to determine details of the microstructure of plastically deformed alloys. Four different alloys were deformed by uniaxial tension and compression to a range of strains. The methods we have considered include, the full-width, Williamson-Hall methods, Warren-Averbach methods, and van Berkum's alternative method. Different metals were chosen to understand the effect of the deformation microstructure and crystal structure, a nickel alloy, two stainless steel alloys and two titanium alloys. The dislocation density values found by Williamson-Hall and Warren-Averbach methods were found to be close to those expected from TEM results of similar metals. When using the Warren-Averbach methods the results suggest that systematic errors in the dislocation density are introduced by three main factors: (1) separation of instrumental broadening, (2) separation of size and strain broadening, and (3) separation of dislocation density and arrangement. Which suggests in many cases the simpler Williamson-Hall method may be preferable. The other main parameters that can be determined by DPPA are the crystal size and the dislocation arrangement. The work suggests that further investigation is needed to understand what use if any these parameters have for quantifying the deformed microstructure of plastically deformed metals. Graphical abstract: Highlights: The Williamson-Hall method produced dislocation density values more consistent with expectations than the Warren-Averbach method. The procedure for separation of different components that contribute to broadening, can cause errors most notably for Fourier methods. The size value obtained by most diffraction peak profile analysis methods is not helpful in quantifying a deformed metal. The alternative method, an exception to the above, provides size values that can be related to an effective crystal size in deformed metals.